Nationhood in world politics - Wan Hashim Haji Wan Teh Profesor Emeritus Dato' Dr. 1949-; Wan Norhasniah Wan Husin
This is the complication of essays and lecture notes to meet the need of students at UPNM who are registered for the subject of Nationhood in World Politics which is a university subject newly introduced since the first semester of academic session 2014/15.